Removal of Ni(II) from Aqueous Medium Using Low Cost Adsorbent - Kulkarni, J.R.; Shrivastava, V.S. (Asian Journal of Chemistry, 2010)
The adsorption technique using coconut husk was applied for the removal of Ni2+ ions from aqueous samples. The dried and powdered husk was contacted with acidified formaldehyde and the product so obtained is highly efficient in adsorbing Ni2+ ions from the solutions. The extent of removal/adsorption was dependent upon the pH, amount of adsorbent used and the time of contact The sorbent is effective for quantitative removal of Ni2+ ions in alkaline conditions and equilibrium has been achieved in 1 h. This method is quite feasible, economic, time saving and low cost.